Caught in a Productivity Trap : A Distributional Perspective on Gender Differences in Malawian Agriculture - Kilic, Talip; Palacios-Lopez, Amparo; Goldstein, Markus (World Bank, Washington, DC, 2016)
The vast majority of households in Malawi are involved in agriculture, and improving agricultural productivity, particularly for women, who tend to attain lower yields than men, could lead to significant poverty reduction and improvements in gender equality. This study asks two main questions: (1) exactly how great are the differences in agricultural productivity between men and women in Malawi? And (2) how much of the gender gap is explained by differences in levels of agricultural inputs vs. differences in returns to these inputs? The author trace the varying constraints faced by farmers at different levels of productivity, as well as at average productivity, a level of analysis that is crucial for designing effective interventions aimed at bridging the gender gap. We find that on average, female-managed plots are 25 percent less productive than plots managed by males. Further, the gender gap widens significantly as agricultural productivity increases. More than 80 percent of the mean gender gap is explained by differences in levels of agricultural inputs, suggesting that addressing market and institutional failures underlying these differences could have direct economic benefits.